PERBEDAAN KADAR KETON URIN PADA PEMERIKSAAN SEGERA DENGAN PEMERIKSAAN YANG DITUNDA - Kahar, Hartono (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PERBEDAAN KADAR KETON URIN PADA PEMERIKSAAN SEGERA DENGAN PEMERIKSAAN YANG DITUNDA Dr. dr Hartono Kahar, Sp.PK. MQIH Prodi D3 Analis Kesehatan UNMUH Surabaya AbstractUrine examination is a common examination done by a health care analyst at the laboratory. From the results of this examination can know about kidney disorders, urinary tract and some metabolic functions of the body. The length of delay in the laboratory examination of urine greatly affect the results of the analysis, it is because some of the content in the urine may change in case of delay in the examination, such as ketones. The volatile nature of the ketone, the urine is used fresh urine. In clinics and hospitals in general, there is still a delay examination of the urine. Formulation of the problem in this study is whether there are differences in levels of ketones urine examination on examination with the examination immediately suspended, while the purpose of this study to investigate the influence of long delays on the results of urine ketone levels. The hypothesis of this research is that there are differences in levels of ketones in the urine examination with the examination immediately suspended. The research method used was experimental. The population of this research is all the urine that has been available in hospital laboratories Pamekasan district that has shown positive results ketones with accidental sampling technique. The variable in this study was the examination time and urine ketone levels with a sample of 16 urine samples. From the results of the study with a 30-minute time delay obtained 14 urine samples (87.5%) with high levels of ketones and 2 negative urine samples (12.5%) with very low levels of ketones. From the results of these data, wilxocon tested and the results obtained with a value of Z = -3.624 significant value 0.000 <0.05 or 5%, so it can be concluded that there are differences between the levels of ketones urine samples examined immediately by a delayed.Key word : Urine examination, ketones